The Classicality and Quantumness of the Driven Qubit–Photon–Magnon System - Maged Faihan Alotaibi; Eied Mahmoud Khalil; Mahmoud Youssef Abd-Rabbou; Marin Marin (Mathematics, 2022)
The hybrid architecture of the driven qubit–photon–magnon system has recently emerged as a promising candidate for novel quantum technologies. In this paper, we introduce the effective wave-function of a superconducting single qubit and a magnon mode contained within a cavity resonator and an external field. The non-classicality of the magnon and resonator modes are investigated by using the negative values of the Wigner function. Additionally, we discuss the non-classicality of the qubit state via the Wigner–Yanase skew information. We find that the mixture angle of the qubit–resonator plays a controllable role in non-classicality. However, the strength of the magnon–photon increases the non-classical behaviour of the system.